2009
DOI: 10.1080/00365520802400826
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2, multidrug resistance 1, and breast cancer resistance protein gene polymorphisms and inflammatory bowel disease in the Danish population

Abstract: An effect of the COX-2 polymorphism on both CD and UC was shown which is compatible with the presence of a recessive allele in linkage equilibrium with the SNP marker in the COX-2 gene. The polymorphism located in intron 3 of the MDR1 gene showed a weak association with CD, and a marginally suggestive association with UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 45 publications
3
29
1
Order By: Relevance
“…On the other hand, our control group data on the COX-2 -765 genotype were in good agreement with other European control data recently reported from Denmark, being 73.2%, 24.8% and 2.0% for -765 GG, GC and CC genotypes, respectively [16] . In addition, the COX-2 polymorphism data in our patients are very similar to the recently reported COX-2 -765 and -1195 genotype distributions in Dutch esophageal adenocarcinoma patients by Moons et al [17] , except for the -1195 GG genotype, which was present in 8.0% of our patients vs only 2.0% in the patients in the study by Moons et al [17] .…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, our control group data on the COX-2 -765 genotype were in good agreement with other European control data recently reported from Denmark, being 73.2%, 24.8% and 2.0% for -765 GG, GC and CC genotypes, respectively [16] . In addition, the COX-2 polymorphism data in our patients are very similar to the recently reported COX-2 -765 and -1195 genotype distributions in Dutch esophageal adenocarcinoma patients by Moons et al [17] , except for the -1195 GG genotype, which was present in 8.0% of our patients vs only 2.0% in the patients in the study by Moons et al [17] .…”
Section: Discussionsupporting
confidence: 80%
“…Fiedler et al [41] found a similar association, most notably for the MDR1 2677GG / 3435TT haplotype with UC, but not for CD. The haplotypes investigated by Ho et al [23] showed positive (MDR1 G2677 / 3435T) and negative (MDR1 2677T / C3435) correlations with UC, and confirmed the findings of Fiedler et al [42] Haplotypes including BCRP C421A have been less frequently assessed and no associations with a combined IBD endpoint are known of to date.…”
Section: Haplotype Studiessupporting
confidence: 70%
“…Genomic DNA was isolated from blood samples according to standard procedures with minor modifications as described previously [28]. All analyses were run blinded to the case-control status.…”
Section: Methodsmentioning
confidence: 99%